Post‐Acquisition Retention of Target Founder‐CEOs: Looking Beneath the Surface. (7th September 2021) - Aghasi, Keivan; Colombo, Massimo G.; Rossi‐Lamastra, Cristina
Abstract: This study investigates the retention of target CEOs in the aftermath of acquisitions by comparing target founder and professional CEOs. Considering insights from resource‐based view, managerial rent perspective, studies on acquisition implementation, and the literature on founder‐CEOs, we argue that target founder‐CEOs are resourceful assets for acquirers for implementation purposes; ergo, they are more likely to be retained than target professional CEOs. Target founder‐CEOs, owing to their unique firm‐specific human capital, have greater acquisition implementation abilities than target professional CEOs. They also have greater monetary incentives to deploy their implementation abilities to the benefit of acquirers. Furthermore, we claim that these effects are stronger, thus contributing to a higher retention rate of target founder‐CEOs than their professional peers when acquisitions are technology‐driven, and target firms are young. Results from a sample of small high‐tech firms acquired by large incumbent firms confirm our predictions.